Lectures on the Will to Know - Foucault, M. author. aut Link
XV, 293 p.
Keywords: In the first of his annual series of lectures at the Collège de France, Foucault develops a vigorous Nietzschean history of the will to know through an analysis of changing procedures of truth, legal forms, and class struggles in ancient Greece.